Corrosion Damage Analysis of Steel Frames Considering Lateral Torsional Buckling. (2017) - Secer, Mutlu; Uzun, Ertugrul Turker
Abstract: There is an increasing recognition that the conventional design of steel buildings for collapse prevention is not sufficient for the necessities of the modern society. Structural designs that account durability and sustainability issues have gained attention. Beside all the advantages of steel structures, there are some drawbacks which are mainly related to deterioration especially in terms of corrosion. Corrosion problem is associated to the huge economic, social and environmental losses for steel constructions which should be investigated from all perspectives. In this study, steel frame structures are investigated under deterioration due to corrosion and nonlinear analysis are performed considering lateral torsional buckling. Numerical examples are provided in order to determine and evaluate the structural behavior under corrosion. Considering both corrosion and lateral torsional buckling in structural analysis decrease the load carrying capacity significantly and reveal the importance of corrosion in terms of structural behavior. The results of this study provide information about the decrease of the structural performance due to deterioration and underlines that steel frames that are under corrosion risk may not able to be fulfill their desired performance levels before their service life have expired.